2022
DOI: 10.3389/fneur.2022.916990
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sensory Observation and Somatosensory Stimulation in Mirror Neurons and the Sensorimotor Network: A Task-Based fMRI Study

Abstract: ObjectiveThis study aimed to investigate brain plasticity by somatosensory stimulation (SS) and sensory observation (SO) based on mirror neuron and embodied cognition theory. Action observation therapy has been widely adopted for motor function improvement in post-stroke patients. However, it is uncertain whether the SO approach can also contribute to the recovery of sensorimotor function after stroke. In this study, we explored the therapeutic potential of SO for sensorimotor dysfunction and provided new evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…Our previous study found that the precentral gyrus, supplementary motor area and postcentral gyrus could be activated in somatosensory stimulation (SS) and sensory observation (SO) in healthy subjects. 58 These brain regions are responsible for movement execution, movement preparation and sensory integration. 59 60 Evidence from animal and clinical studies suggests that the activation of these brain regions contributes to functional reorganisation after stroke.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study found that the precentral gyrus, supplementary motor area and postcentral gyrus could be activated in somatosensory stimulation (SS) and sensory observation (SO) in healthy subjects. 58 These brain regions are responsible for movement execution, movement preparation and sensory integration. 59 60 Evidence from animal and clinical studies suggests that the activation of these brain regions contributes to functional reorganisation after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…65 In addition, SS showed increased activation of the thalamus and insula. 58 The thalamus and insula are considered integration centres that integrate diverse information, such as motor, sensory, emotional and social information, that is processed throughout the cerebral cortex. [66][67][68] Furthermore, the thalamus is also associated with prognosis and recovery after stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a noninvasive neuroimaging technology, functional magnetic resonance imaging (fMRI) lays the foundation for real-time measurement of whole-brain activity and helps advance the understanding of neuroplasticity modulated by acupuncture [16,17]. Neuroimaging evidence has demonstrated the facilitating effect of acupuncture in the regulation of brain functional reorganization, comprising activation of motor-related cortical areas [18][19][20], increasing motorcognition connectivity and decreasing compensation of contralesional motor cortex, and modulating effective connectivity of resting-state networks in patients with poststroke hemiplegia [21,22].…”
Section: Introductionmentioning
confidence: 99%